Comments on “Is Copytus Skogsberg, 1939 (Crustacea: Ostracoda) a neocytherideid? With description of a new family and two new species” by Coimbra, Bergue & Ramos (2020) - Külköylüoğlu, Okan (Zootaxa, 2021)
Most recently, Coimbra et al. (2020) published an article in this journal (Zootaxa, 4729 (2): 177–194) questioning the taxonomic position of the genus Copytus Skogsberg, 1939 (Crustacea, Ostracoda) along with proposing it as the type genus of their new family (Copytidae Coimbra et al., 2020), and erecting two new species that were listed by previous authors as Copytus sp. 1 and Copytus sp. 2. The main diagnostic characteristics of their new proposed family (and the genus Copytus) are the hinge type and muscle scars on the carapace and/or valves (see lines 6–8 from the bottom, p. 179 in Coimbra et al. 2020). They also underlined that (p. 179) “...this study is based exclusively on the morphology of the animals’ hard parts”. While the authors considered another genus (Neocopytus) proposed by Külköylüoğlu, Colin & Kılıç (2007) of the family Neocytherididae as invalid, they interestingly transferred some species of Neocopytus to Copytus as species of their new family (Coimbra et al. 2020). Herein, my point with the comments listed below is to clarify that, when possible, both soft and hard parts should be considered in taxonomy, and such an integrated approach clearly indicates that Neocopytus is a valid and taxonomically useful genus.